Stochastic Extension to Statecharts for representing performance models: an application to a file system - Francês, Carlos Renato Lisboa; Vijaykumar, Nandamudi Lankalapalli; Santana, Marcos José; Carvalho, Solon Venâncio de; Santana, Regina Helena Carlucci (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance Computing, 2000)
The paper aims to present that another high-level specification tool Statecharts may also be used to represent performance models. Statecharts may be considered as an extension of state-transition diagrams added with the concepts of hierarchy and parallelism. The Statecharts specification has to treated in the sense performance measurements are to be obtained. This is done by generating Statecharts equivalent of state-transition diagrams. By associating the resulted state-transition diagrams to a Markov chain and using an analytical numerical method, performance measurements are obtained. A performance model represented in queuing networks, Petri nets and Statecharts will be discussed.